APLIKASI INTERPOLASI LAGRANGE TERHADAP EFISIENSI TURBIN PADA PABRIK KELAPA SAWIT MAYANG KAPASITAS 40 TON/JAM - Siti Aisyah Aisyah; Zulham Effendi; Dicky Vernanda Maha (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Energy can’t be created and can’t be destroyed but energy can be transformed from one energy into another. The success rate of energy change is called efficiency. The success of a steam turbine certainly can’t be separated from the level of efficiency and application of good and correct procedures in its use. Efficiency values can be found by using data from the power released by the turbine, mass flow rate andenthalpy. Enthalphi search can use the lagrange interpolation method. Data is collected for 3 months in September, October and November 2018 at the Mayang palm oil mill. The greatest efficiency value in the three months occurred in October, amounting to 43.50 % and the lowest occurred in November, amounting to 36.98 %. High or low efficiency can occur because of the large and small comparison of the power released by the turbine enthalpy and mass flow rate. As well as the effect of the wet steam produced by the boiler can cause rotation of the blades to weaken and result in little power released by the steam turbine.